2020
DOI: 10.18805/lr-540
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Enhances Salt Tolerance through Regulating Antioxidant Enzyme Activity and Nutrient Uptake in Pea

Abstract: Background: Salinity is one of the environmental stress factors that restrict the crop production by endangering agricultural areas. Nitric oxide (NO) protects plants from damage caused by oxidative stress conditions in various biological ways. Methods: In this greenhouse investigation during 2018, pea plants were irrigated with three levels of NaCl (0, 50 and 100 mM) solutions. NO solutions were prepared with three different doses (0, 75 and 100 µM SNP). These solutions were applied to the seeds before sowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…The obtained results are in harmony with earlier investigations on maize, sorghum, tomato, mustard, barley, and pea plants under salt stress [15,[65][66][67][68][69][70][71]. Our data (Figure 1) are also in accordance with previous studies on soy bean and pea plants under salt stress [72,73], which have shown that treatment with SNP prevents a salt-induced reduction of the leaf pigment content. SNP application alleviated the salt-induced decrease in chlorophyll synthesis, and enhanced the accumulation of the light-harvesting chlorophyll a/b complex of PSII (LHCII) and PSIA/B in barley seedlings [74].…”
Section: Discussionsupporting
confidence: 93%
“…The obtained results are in harmony with earlier investigations on maize, sorghum, tomato, mustard, barley, and pea plants under salt stress [15,[65][66][67][68][69][70][71]. Our data (Figure 1) are also in accordance with previous studies on soy bean and pea plants under salt stress [72,73], which have shown that treatment with SNP prevents a salt-induced reduction of the leaf pigment content. SNP application alleviated the salt-induced decrease in chlorophyll synthesis, and enhanced the accumulation of the light-harvesting chlorophyll a/b complex of PSII (LHCII) and PSIA/B in barley seedlings [74].…”
Section: Discussionsupporting
confidence: 93%
“…However, exogenous NO alleviated this effect [ 40 ]. Similarly, NO application increased the chlorophyll content in salt-stressed pea, bermudagrass, and soybean plants [ 41 , 42 , 43 ]. Moreover, although the chloroplast thylakoid system is distorted in salinized plants, combined SNP and S supplementation positively affected the chloroplast structure in salinized mustard plants, restoring them to a normal shape, and the thylakoid system was appropriately rearranged [ 44 ].…”
Section: No Alleviates Salt Stress-induced Damagementioning
confidence: 99%
“…NO is a powerful inhibitor of ROS, which can cause lipid peroxidation. SNP application has been shown to decrease the contents of H 2 O 2 , superoxide anion, and MDA in NaCl-stressed pak choi, pepper, mustard, pea, eggplant, tomato, spinach, and barley plants, thereby preventing oxidative damage [ 21 , 34 , 39 , 40 , 41 , 53 , 58 , 59 ].…”
Section: No Alleviates Salt Stress-induced Damagementioning
confidence: 99%
“…It was found that there was no germination at 200 mM salt concentration in peas and a decrease in the germination characteristics of both species with increasing salt concentration (Dadasoglu et al 2020). Studies conducted with peas indicate that salt stress negatively affects plant growth (Kaya, 2021;Dadasoglu et al 2021; Effect of Different Bacterial Strains on the Germination Forage Pea (Pisum sativum ssp. arvense L.) under Salt Stress Prakash et al 2021).…”
Section: Fig 3: Effect Of Salt Stress and Bacteria Application On Mdg...mentioning
confidence: 99%